2014
DOI: 10.1037/a0034806
|View full text |Cite
|
Sign up to set email alerts
|

Symptom dimensions of anxiety following myocardial infarction: Associations with depressive symptoms and prognosis.

Abstract: ObjectiveDifferential associations of symptom dimensions with prognosis in myocardial infarction (MI) patients have been shown for depression, but no studies have focused on anxiety dimensions.The aim of this study was to assess the association between somatic and psychological symptoms of anxiety following acute MI with adverse prognosis and to assess the overlap between anxiety and depression dimensions. MethodsPatients (n=418) were assessed on demographic and clinical variables. The Hamilton Anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
3
31
0
Order By: Relevance
“…The relation between MI and psychiatric disorders has already been described [22,23] but it is also known that psychiatric patients have higher chance of cardiovascular risk factors [24], unlike what was shown in this study, MINOCA patients had a better cardiovascular profile. Recently, a study suggested that optimistic patients have a better prognosis after MI [25], while others linked heart disease with a worse outlook [26,27]. This concurs with the present hypothesis that negative emotions could be a risk factor for MINOCA.…”
Section: Discussionsupporting
confidence: 91%
“…The relation between MI and psychiatric disorders has already been described [22,23] but it is also known that psychiatric patients have higher chance of cardiovascular risk factors [24], unlike what was shown in this study, MINOCA patients had a better cardiovascular profile. Recently, a study suggested that optimistic patients have a better prognosis after MI [25], while others linked heart disease with a worse outlook [26,27]. This concurs with the present hypothesis that negative emotions could be a risk factor for MINOCA.…”
Section: Discussionsupporting
confidence: 91%
“…Our current findings show that anxiety was strongly associated with dyspnea complaints in the fully adjusted model. We used the Hamilton anxiety rating scale to assess anxiety, which does contain a somatic component (22). In search of a mechanism, we split up somatic and cognitive anxiety symptoms, and found that cognitive anxiety symptoms are not associated with dyspnea, while somatic symptoms, especially related to cardiovascular (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Somatic and cognitive subscale scores have been calculated by summing the items belonging to these symptom dimensions (22). In the current dataset, Cronbach's alpha was .80 at baseline and .78 at 12 months follow-up.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Fear disorders are further specifically characterized by underlying symptom dimensions of somatic arousal and phobic fear. These characteristics have been repeatedly shown to predict incident CHD (Albert et al, 2005; Nabi et al, 2010) and CHD prognosis (Watkins et al, 2010; Roest et al, 2014), although not all study results have been consistent. In a relatively small sample of patients who were assessed for anxiety and depression before undergoing coronary artery bypass graft surgery, neither fear disorder (a cluster including PD, agoraphobia and SAD) nor anxious arousal was predictive of cardiovascular and cerebrovascular events.…”
Section: Discussionmentioning
confidence: 94%
“…In this model GAD is classified as a distress disorder since it is more strongly linked to depression than to fear disorders, which are characterized by phobic fear and somatic arousal (Clark & Watson 1991; Watson 2005; Brown & McNiff 2009; Den Hollander-Gijsman et al, 2010). Phobic fear and somatic arousal may be particularly strongly related to the development of heart disease and adverse prognosis in patients with CHD (Albert et al, 2005; Watkins et al, 2010; Nabi et al, 2010; Roest et al, 2014). Therefore, categorizing depressive and anxiety disorders into fear and distress disorders may be more useful than comparing anxiety and depressive disorders, or examining all disorders separately, when investigating the association between these disorders and heart disease.…”
Section: Introductionmentioning
confidence: 99%